2017
DOI: 10.3389/fneur.2017.00619
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Inner and Outer Retinal Layer Abnormalities in Eyes with Permanent Temporal Hemianopia from Chiasmal Compression

Abstract: PurposeThe aims of this study are to compare optical coherence tomography (OCT)-measured macular retinal layers in eyes with permanent temporal hemianopia from chiasmal compression and control eyes; to compare regular and slow-flash multifocal electroretinography (mfERG) in patients and controls; and to assess the correlation between OCT, mfERG, and central visual field (SAP) data.MethodsForty-three eyes of 30 patients with permanent temporal hemianopia due to pituitary tumors who were previously submitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
8

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 70 publications
2
18
1
8
Order By: Relevance
“…Another study involving 43 eyes with permanent hemianopsia also reported thinning of RNFL, GCL and IPL in all regions similar to our study (de Araujo et al. ). In our study, the thickness of RNFL, GCL, IPL and IRL decreased in patients with chiasmal compression compared with the control group at 1 year postoperatively, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another study involving 43 eyes with permanent hemianopsia also reported thinning of RNFL, GCL and IPL in all regions similar to our study (de Araujo et al. ). In our study, the thickness of RNFL, GCL, IPL and IRL decreased in patients with chiasmal compression compared with the control group at 1 year postoperatively, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…; de Araujo et al. ). These studies also revealed inner nuclear layer (INL) thickening (Monteiro et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…• With multifocal visual-evoked potentials, it can be used to analyse mfERG, mfVEP or mfPERG 8,9,10,13,17,20,25,28,34,37,42,45,49,52,53,54,55 0:5125 0:5328 0:5438…”
Section: Discussionmentioning
confidence: 99%
“…Another study [6] concludes that using the central ring in mfERGs is an appropriately sensitive technique with which to study the progression of age-related macular degeneration over short periods of time. Analysis by quadrant makes it possible to carry out comparisons between mfERG studies and optical coherence tomography (OCT) [7,8]. It is also common to find the results of clustering by ring and quadrant in publications that analyse the technical aspects of mfERG [9,10].…”
Section: Introductionmentioning
confidence: 99%